A Novel, Simple, and Flexible Fault-Tolerant Control Algorithm for Multiphase Electrical Machine Operation Under Open Circuit Faults - Massimo Caruso; Antonino Oscar Di Tommaso; Rosario Miceli (IEEE Access, 2024)
This paper presents a novel and simple procedure for the determination of a Fault-Tolerant Algorithm (namely FTA) for the adequate working operation of an electric machine equipped with a general $m$ -phase winding under possible open circuits occurring in some of its phases. The FTA is firstly theoretically derived from the analysis of the magnetic field distribution in polyphase systems, then simulated through finite-element analysis and finally implemented via software for real-time validation. The effectiveness of the proposed procedure is confirmed through experimental tests on a laboratory setup. Key contributions include the flexibility of the algorithm, which can be applied to any $m$ -phase electric machine with various winding configurations. Both the obtained FEA and experimental results demonstrate that the proposed control algorithm can be easily used and applied in electric drives supplied by $m$ -phase motors under fault conditions without significantly affecting the magnetic performance of the whole system and ensuring the continuity of operation even in the presence of faults.